Synchronous mantle cell lymph node lymphoma and pulmonary adenocarcinoma: a case report with literature review. (28th September 2015) - Braham, Emna; Zarrouk, Mourad; Mlika, Mouna; Kilani, Tarek; El Mezni, Faouzi
Abstract: Background and Aims: Coexistence of mantle cell lymphoma and lung adenocarcinoma is extremely rare. The aim of this study is to present the first case of incidental discovery of primary lung adenocarcinoma associated to lymph node mantle cell lymphoma. Methods: A 45 year‐old man, admitted for inguinal mass appeared since three months. Physical examination showed a 1 cm axillary and 3 cm inguinal adenopathies which were hard and fixed. A biopsy of inguinal mass revealed mantle cell lymphoma. Assessment of disease extension found a right superior lobe tumor with mediastinal lymphadenopathies. Fibreoptic bronchoscopy was normal. A fine needle biopsy of lung tumor was performed to determinate the nature of the pulmonary lesion. Histopathological findings were consistent with primary poor differentiated pulmonary adenocarcinoma with TTF‐1 expression. A first mediastinoscopy was realized to verify mediastinal lymphadenopathies; frozen section showed a mantle cell lymphoma. A right lobectomy was then performed confirming the diagnosis of lung adenocarcinoma. Then, the patient was treated for the mantle cell lymphoma by 6 cures of alternating RCHOP and RDHAP (dexamethasone, high‐dose Ara‐Cytarabine and cisplatin) regimens followed by autologous stem cell transplantation. Results: The patient died because of treatment complications 3 years after diagnosis. Conclusion: Progresses are necessary to understand the pathogenesis of of synchronous occurrence of both diseases.